Self-Concept of Adolescent Girls Who Dropped Out of School Due to Early Marriage - Noviatul Rahmadanti; M. Fahmi Aufar Asyraf (International Conference on Sustainable Health Promotion, 2025)
This study analyzes the self-concept of adolescent girls who dropped out of school due to marrying at a young age. The research method employed a qualitative phenomenological approach, using in-depth interviews and observations involving three subjects in Rejeni Village, Krembung District, Sidoarjo Regency. The findings revealed that early marriage influences their self-concept in various aspects, including self-identity, behavior, self-evaluation, body image, ethics, family roles, and social roles. The respondents faced significant challenges in adjusting to their new responsibilities, such as becoming a wife and mother, which affected their self-confidence, academic opportunities, and social adaptation.